Emergency Department triage systems - Koroni, Aristea; Kelesi, Martha; Kalemikerakis, Ioannis; Papageorgiou, Dimitris; Vassilopoulos, George (Health & Research Journal, 2017)
Introduction: In recent decades, it is observed a significant increase in the number of patients who visit Emergency Departments (ED). Therefore, it is imperative to adopt an effective triage system. Aim: The aim of the present systematic review was to explore the available Triage Systems for EDs. Material and Method: A systematic literature review in international databases (PubMed and Scopus) between January 2017 and April 2017. During the initial research 3462 articles were indetified, however only 11 met the inclusion criteria. Results: The most common triage systems in Emergency Departments are the Australasian Triage Scale, the Canadian Emergency Department Triage and Acuity Scale (CTAS), whereas the use of the Manchester Triage System is limited mainly due to its complexity. The application of the Emergency Severity Index (ESI) tends to be increased because of its advantages compared to other systems. It is important to mention that no study has been found in Greece to explore the triage system in ED. Conclusions: There are many scales and systems available for the effective triage in EDs and nurses play significant role in their implementation. Moreover, it is important the authorities to establish legislation in Greece so as effective triage systems to be applied in Greek hospitals.